Algebra
- If x = 999, y = 1000, z = 1001, then the value of
x³ + y³ + z³ - 3xyz is : x - y + z
-
View Hint View Answer Discuss in Forum
x³ + y³ + z³ – 3xyz = 1/2 (x + y + z) {(x – y)² + (y – z)² + (z – x)²}
∴ x³ + y³ + z³ – 3xyz x - y + z = 1/2(x + y + z){(x-y)² + (y-z)² + (y-z)² + (z-x)²} x - y + z = 1 (999 + 1000 + 100) = {999 + 1000)² + (1000 - 10001)² + (1001 + 999)²} 2 (999 - 1000 + 1001) = 3000 × (1 + 1 + 4) 2 × 1000 = 18 = 9 2 Correct Option: D
x³ + y³ + z³ – 3xyz = 1/2 (x + y + z) {(x – y)² + (y – z)² + (z – x)²}
∴ x³ + y³ + z³ – 3xyz x - y + z = 1/2(x + y + z){(x-y)² + (y-z)² + (y-z)² + (z-x)²} x - y + z = 1 (999 + 1000 + 100) = {999 + 1000)² + (1000 - 10001)² + (1001 + 999)²} 2 (999 - 1000 + 1001) = 3000 × (1 + 1 + 4) 2 × 1000 = 18 = 9 2
- If a + b + c = 0, then the value of (a³ + b³ + c³) is
-
View Hint View Answer Discuss in Forum
If a + b + c = 0 then, a³ + b³ + c³ = 3abc
∵ a³ + b³ + c³ – 3abc = (a + b + c) (a² + b² + c² – ab – bc – ac)Correct Option: C
If a + b + c = 0 then, a³ + b³ + c³ = 3abc
∵ a³ + b³ + c³ – 3abc = (a + b + c) (a² + b² + c² – ab – bc – ac)
-
If x² – 4x + 1 = 0, then the value of x6 + 1 is : x³
-
View Hint View Answer Discuss in Forum
x² – 4x + 1 = 0
⇒ x² + 1 = 4x⇒ x² + 1 = 4x x x ⇒ x + 1 = 4 x
On cubing both sides,x + 1 ³ = 64 x x³ + 1 + 3 x + 1 ³ = 64 x³ x ⇒ x³ + 1 + 3 × 4 = 64 x³ ⇒ x³ + 1 = 64 - 12 = 52 x³ ⇒ x6 + 1 = 52 x³ Correct Option: B
x² – 4x + 1 = 0
⇒ x² + 1 = 4x⇒ x² + 1 = 4x x x ⇒ x + 1 = 4 x
On cubing both sides,x + 1 ³ = 64 x x³ + 1 + 3 x + 1 ³ = 64 x³ x ⇒ x³ + 1 + 3 × 4 = 64 x³ ⇒ x³ + 1 = 64 - 12 = 52 x³ ⇒ x6 + 1 = 52 x³
- If x = 93, y = 93, z = 94 then the value of (x² – y² + 10xz + 10yz) is
-
View Hint View Answer Discuss in Forum
x² – y² + 10xz + 10yz
⇒ (x + y) (x – y) + 10z (x + y)
= (x + y) (x – y + 10z)
= (93 + 93) (93 – 93 + 10 × 94)
= 186 × 940 = 174840Correct Option: C
x² – y² + 10xz + 10yz
⇒ (x + y) (x – y) + 10z (x + y)
= (x + y) (x – y + 10z)
= (93 + 93) (93 – 93 + 10 × 94)
= 186 × 940 = 174840
- If x = 222, y = 223, z = 225 then the value of (x³ + y³ + z³ + 3xyz) is :
-
View Hint View Answer Discuss in Forum
x³ + y³ + z³ – 3xyz
= 1 (x + y + z){(x-y)² + (y-z)² + (z-x)²} 2 = 1 (222 + 223 + 225){(222-223)² + (223-225)² + (225-222)²} 2 = 1 × 670(1 + 4 + 9) 2 = 670 × 14 = 4690 2
Correct Option: B
x³ + y³ + z³ – 3xyz
= 1 (x + y + z){(x-y)² + (y-z)² + (z-x)²} 2 = 1 (222 + 223 + 225){(222-223)² + (223-225)² + (225-222)²} 2 = 1 × 670(1 + 4 + 9) 2 = 670 × 14 = 4690 2